Design and performance evaluation of electromechanical impedance instrumented quantitative corrosion measuring probe based on conical rods. (1st December 2022) - Wang, Jianjun; Wen, Lijie; Liu, Zhishun; Luo, Mingzhang; Jia, Sihui; Li, Weijie; Lan, Chengming
Abstract: Previous study has proved that using electromechanical impedance instrumented bar-type corrosion measuring probe can realize the quantitative assessment of the corrosion amount. To gain more insights into the working mechanism and design better probes, this work examined a new type of corrosion measuring probe based on the conical rod, and evaluated their performance. Theoretical model of this type of new probes was established based on one dimensional piezo-elasticity theory, and the electrical impedance was derived to obtain first resonant and anti-resonant frequencies in longitudinal vibration mode. Two experiments were performed to validate the feasibility of the probe for corrosion measurement, including the artificial uniform corrosion experiment and the accelerated corrosion test. Comparisons between the theoretical predictions and the experimental results from the artificial uniform corrosion experiment were made, and good agreement was found. Effects of piezoelectric patch thickness and cone angle on first resonant and anti-resonant frequencies were also analyzed. In addition, a wireless impedance measurement system was preliminarily realized, which is very promising in developing the low cost and high accuracy online real-time monitoring technology for the pipeline corrosion monitoring.